Rolf Harris the wizard of Aus. - Rolf Harris Enterprises (Northampton, England : Rolf Harris Enterprises Ltd., 1999)
This site contains biographical information, music, cartoons and related merchandise by and of the Australian entertainer Rolf Harris. It also includes links to other related and fan sites.
System requirements: Sound player for WAV or MP3 files
Title from title screen (viewed on June 27, 2000).
Text, graphics and music.
Mode of access: Internet via World Wide Web. Available at: http://www.rolfharris.com/index.html
Selected for archiving
Keywords: Harris, Rolf, -- 1930-; Entertainers -- Australia